2016
DOI: 10.1186/s12884-015-0735-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up and pregnancy after complete sacrectomy with lumbopelvic reconstruction: case report and literature review

Abstract: BackgroundSacrectomy remains a technically complex procedure for resection of malignant pelvic neoplasia. Commonly, postoperative complications include permanent neurological deficits. Only a few studies have reported the long-term functional outcomes of patients who had undergone sacrectomy.Case presentationWe previously reported on the utilization of complete sacrectomy and lumbopelvic reconstruction for the management of primary myofibroblastic sarcoma of the sacrum and ilium in a 15-year-old female patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
208
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(241 citation statements)
references
References 6 publications
27
208
6
Order By: Relevance
“…Currently, this appears to be lacking in both regions of Nigeria, and would be crucial if Nigeria is to achieve the Sustainable Development Goal of reducing the ratio of maternal deaths to 70 deaths per 100,000 live births by 2030. One study has advocated geospatial mapping of hotspot areas, where women mostly give birth at home, as a key strategy to improving the use of maternal health services [ 15 ]. Findings of the present study does emphasise this approach to improving the use of essential maternal healthcare services and preventing maternal deaths.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, this appears to be lacking in both regions of Nigeria, and would be crucial if Nigeria is to achieve the Sustainable Development Goal of reducing the ratio of maternal deaths to 70 deaths per 100,000 live births by 2030. One study has advocated geospatial mapping of hotspot areas, where women mostly give birth at home, as a key strategy to improving the use of maternal health services [ 15 ]. Findings of the present study does emphasise this approach to improving the use of essential maternal healthcare services and preventing maternal deaths.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of the impact of user fees exemption for maternal health on inequality in access to maternal health is scanty and inconsistent. There is evidence that free maternal healthcare reduces [ 9 , 14 ], widens [ 15 18 ], and fail to impacts [ 5 , 10 , 19 ] inequality in access to maternal healthcare services. While one study reported that the rate of increase in the use of maternal healthcare services was highest among women in the lowest income strata following the removal of user fees [ 9 ], other studies provide contradictory evidence and even assert that free maternal health intervention benefits women in high and middle income categories more than low-income earners [ 10 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) emphasises that violence by men towards women is a significant health problem affecting one in three women globally [19]. Addressing violence against women is critical for both health and family reasons [2225]. Research has shown that male intimate partner violence against women can increase when the husband experiences a loss of power and lack of control in addition to socioeconomic poverty; moreover, women’s increased educational level and power position might provoke men [26].…”
Section: Introductionmentioning
confidence: 99%
“…Stress caused by delivery increases release of dynorphin and dopamine, which decreases release of prolactin and delays time to first lactation [ 2 ]. Therefore, time to first lactation is delayed in women who undergo cesarean delivery [ 13 ]. Dexmedetomidine improves time to first lactation by decreasing depression after delivery [ 14 ].…”
Section: Discussionmentioning
confidence: 99%